Sentiment Analysis of Peer-to-Peer (P2P) Lending: A Study of Scientific Publications - Maulida, Syahdatul; Surbakti, Handika (Business and Sustainability, 2023)
The data used in this study includes 200 scientific publications collected during the period 2009 to 2023. The analysis process was carried out by utilizing SentiStrength software, and the results showed that neutral sentiment dominated with a percentage of 38%, followed by negative sentiment of 32%, and positive sentiment of 30%. In more detail, sentiment analysis on scientific publication data fluctuates every year. 2021 recorded the highest number of sentiments, namely 43 sentiments, with the dominance of neutral sentiments as many as 16 sentiments. These findings reflect the dynamics and complexity of views related to peer-to-peer lending in the academic literature. This research contributes to the understanding of how peer-to-peer lending is viewed from the perspective of published literature, by identifying changes in sentiment over time. The implications of these findings can serve as a foundation for further research, as well as provide insights to stakeholders regarding trends and changes in perceptions towards peer-to-peer lending in scholarly publications.